Immigrant entrepreneurs, diasporas and exports - Massimiliano Bratti; Luca De Benedictis; Gianluca Santoni (Publications Office of the European Union, 2018)
In this paper we highlight a new complementary channel to the business and social network effect \~A la Rauch (2001) through which immigrants generate increased export flows from the regions in which they settle to their countries of origin: they can become entrepreneurs. Using very small-scale (NUTS-3) administrative data on immigrants' location in Italy, the local presence of immigrant entrepreneurs (i.e. firms owned by foreign-born entrepreneurs) in the manufacturing sector, and on trade flows in manufacturing between Italian provinces and more than 200 foreign countries, we assess the causal relationship going from diasporas and immigrant entrepreneurs towards export flows. Both the size of the diaspora and the number of immigrant entrepreneurs have a positive, significant and economically meaningful effect on exports. In particular, we find that increasing the stock of (non-entrepreneur) immigrants by 10% would lead to a 1.7% increase in exports in manufacturing, while increasing the number of immigrant entrepreneurs in manufacturing by 10% would raise exports by about 0.6%.
Keywords: F10; F14; F22; R10; 330; exports; immigrants; gravity model; immigrant entrepreneurs; Italy